Occupational asthma from fungicides fluazinam and chlorothalonil. Issue 1 (1st January 2003) - Draper, A; Cullinan, P; Campbell, C; Jones, M; Newman Taylor, A
Abstract : We report two cases of occupational asthma caused by sensitisation to powdered fungicides fluazinam and chlorothalonil, from the same fungicide formulation plant. Both developed work related lower respiratory symptoms after a latent interval of asymptomatic exposure. The diagnosis in each case was confirmed with a serial peak flow record in the workplace followed by specific inhalation tests. These fungicides are known to cause dermatitis; this report indicates that these compounds can induce specific immunological reactions in the airways as well as skin.